Effect of eplerenone on aldosterone and von Willebrand factor levelsin patients with myocardial infarction and chronic kidney disease - V. K. Tashchuk; O. S. Polianska; O. I. Hulaha (Zaporožskij Medicinskij Žurnal)
Aim: to study the levels of aldosterone and von Willebrand factor (VWF) in patients with Q-wave acute myocardial infarction (Q-AMI) and underling chronic kidney disease (CKD) using aldosterone antagonists.